A study on the factors contribute to volunteerism among youth: a case study at Sukarelawan Sahabat Belia, Negeri Melaka / Noor Anida Ibrahim and Nurfathini Mohd Yusni - Ibrahim, Noor Anida; Mohd Yusni, Nurfathini (Faculty of Administrative Science and Policy Studies, 2014)
The purpose of this research is to identify the factors that contribute to volunteerism among youth at Sukarelawan Sahabat Belia, Negeri Melaka. This study is to examine the relationship between several possible several factors that might contribute to volunteerism among youth registered under Sukarelawan Sahabat Belia. The factors which might contribute to volunteerism are self-awareness, family support and community support. From this research, a purposive sampling method was used and 168 respondents were chosen among the volunteers in Sukarelawan Sahabat Belia Melaka. There are several methods and analysis had been done to analyze the data gathered through questionnaire including descriptive statistical analysis, reliability test, Spearman’s bivariate correlation and multiple regression analysis. From the findings, the correlation test clarified that self-awareness, family support and community support influence the youth to contribute in volunteerism. It was found that, the most significant factor that contributes to volunteerism among youth in Sukarelawan Sahabat Belia is family support.